Towards the development of a knowledge management practices survey for application in knowledge intensive organisations - C. Steyn; M. Kahn (South African Journal of Business Management, 2008)
Various surveys of Knowledge Management Practices (KMPs) in private firms show how an increasing awareness of Knowledge Management (KM) is a critical determinant of an organisation's competitiveness. While private sector strategies favouring internal knowledge sharing and external knowledge protection often provide strategic advantage, public sector research organisations such as South Africa's science councils operate in an environment where, for reasons of wider public interest, transparency is encouraged and knowledge is rendered widely accessible. Unfortunately, however, little has been done to develop rigorous measurements of KMPs in such knowledge intensive organisations (KIOs) that primarily engage in knowledge intensive service activities. To complicate matters further, the majority of studies have been inter-organisational and multi-sectoral, focusing on large organisations in the private sector. Few studies have measured perceptions of KMPs amongst employees of a single organisation and even fewer have focused on KMPs within the public sector. This paper will discuss the theoretical and methodological approach used in the development of a survey aimed at measuring employee perceptions of KMPs within the Human Sciences Research Council (HSRC), one of South Africa's largest public KIOs dedicated to `social science research that makes a difference.' Principal component analysis of the survey data revealed six factors or constructs applicable to the measurement of KMPs. The results validate the survey instrument and offer a contribution toward the development of a KMP measurement instrument that may be applied across other KIOs in South Africa.
Keywords: 650